Replacement of Astaxanthin With Lutein in Diets of Juvenile Litopenaeus vannamei: Effects on Growth Performance, Antioxidant Capacity, and Immune Response - Fang, HaoHang; He, XuanShu; Zeng, HuLong; Liu, YongJian; Tian, LiXia; Niu, Jin (Frontiers in Marine Science, 2021)
An eight-week feeding experiment was conducted to investigate whether diet supplementation of lutein could obtain similar growth performance, antioxidant capacity, immunity as well as metabolism of Litopenaeus vannamei compared to dietary astaxanthin. Juvenile L. vannamei (initial body weight: 0.64±0.04g) were fed with one of five isonitrogen and isolipids diets contained with/without lutein or astaxanthin (control group (C) and lutein (L) 1−3 group included 0, 62.5 ppm, 75 ppm, 87.5 ppm lutein respectively, astaxanthin (A) group contained 50 ppm astaxanthin). Results showed that dietary supplementation of lutein ranging from 62.5 to 75 ppm obtained similar growth performance (WGR, SGR, FCR and SR) of L. vannamei compared with the A group (P > 0.05). Apart from that, no statistical difference of antioxidant parameters (hemolymph T-AOC, hemolymph MDA and RNA expression level of GSH-PX, CAT), anti-inflammatory ability (Relish, Rho and HSP70) and apoptosis-related gene expression (Caspase3) were found among lutein ranging from 62.5 to 87.5 ppm and A groups (P > 0.05). These results indicated that a dose of 62.5 to 75 ppm of lutein was suggested to be added in the diet of L. vannamei for substituting dietary astaxanthin.